2016
DOI: 10.1002/art.39447
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Transforming Growth Factor β–Activated Kinase Activation by Epigallocatechin‐3‐Gallate in Rheumatoid Arthritis Synovial Fibroblasts: Suppression of K63‐Linked Autoubiquitination of Tumor Necrosis Factor Receptor–Associated Factor 6

Abstract: Background/Purpose Transforming growth factor β activated kinase 1 (TAK1) is a key MAPKKK family protein in interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), or toll-like receptor signaling. We examined the posttranslational modification of TAK1 and its therapeutic regulation in rheumatoid arthritis (RA). Methods The effect of TAK1, IRAK-1, or TRAF6 inhibition was evaluated in IL-1β-induced human RA synovial fibroblasts (RA-FLS). Western blotting, immunoprecipitation, and 20S proteasome assay were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 51 publications
1
60
0
Order By: Relevance
“…Our initial observations with PDTC suggested that NF-kB is involved in IL-1a expression, which is already known in fibroblast biology (33). We further confirmed this by inhibiting upstream activation of TAK1, a known activator of NF-kBp65 via IL-1b canonical signaling (14). In addition to NF-kBp65, IL-1a has been reported to bind chromatin in mouse macrophages and to associate with p300, both of which were observed in our study (34,35).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our initial observations with PDTC suggested that NF-kB is involved in IL-1a expression, which is already known in fibroblast biology (33). We further confirmed this by inhibiting upstream activation of TAK1, a known activator of NF-kBp65 via IL-1b canonical signaling (14). In addition to NF-kBp65, IL-1a has been reported to bind chromatin in mouse macrophages and to associate with p300, both of which were observed in our study (34,35).…”
Section: Discussionsupporting
confidence: 86%
“…These 2 complexes were subjected to the 100 ns molecular dynamics (MD) simulation. The methodology of MD has been adopted from our previous studies (14). The frames in the trajectory were recorded at 20 ps intervals to study the conformational variations on IL-1a and IL-1b ligand binding.…”
Section: Molecular Dynamics Simulation Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibition of p-c-Jun and NF-κB transcription factors also caused a significant reduction in TNF-α-induced MMP-1 and MMP-13 production in RASFs. We have recently shown that a similar reduction in TRAF6 and TAK1 association by epigallocatechin-3gallate (EGCG) inhibited IL-1β signaling and downstream mediators of inflammation in RASFs (47). It is worth noting that both MMP-1 and MMP-13 have no 3’UTR binding regions for miR-17, which further suggest this to be an indirect regulatory effect on tissue remodeling mediated by RASFs Our results showed that miR-17 targets ASK1 3’UTR to regulate ASK1 expression, which may result in the reduction of p38 and JNK phosphorylation in RASFs.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these proteins, including TRAIL, TGF-b, and PI3K/Akt, have been identified to play role in the pharmacological effects of UA (40,41). Important relevance to RA is the fact that inhibition of these pathways has been shown to reduce inflammation and tissue remodeling in RA (1,19,42). Administration of UA has been shown to reduce significantly the symptoms of arthritis in preclinical models (43,44).…”
Section: Discussionmentioning
confidence: 99%